Quality control in oocytes by p63 is based on a spring-loaded activation mechanism on the molecular and cellular level - Coutandin, Daniel; Osterburg, Christian; Srivastav, Ratnesh Kumar; Sumyk, Manuela; Kehrloesser, Sebastian; Gebel, Jakob; Tuppi, Marcel; Hannewald, Jens; Schäfer, Birgit; Salah, Eidarus; Mathea, Sebastian; Müller-Kuller, Uta; et al. (eLife, 2016)
Mammalian oocytes are arrested in the dictyate stage of meiotic prophase I for long periods of time, during which the high concentration of the p53 family member TAp63α sensitizes them to DNA damage-induced apoptosis. TAp63α is kept in an inactive and exclusively dimeric state but undergoes rapid phosphorylation-induced tetramerization and concomitant activation upon detection of DNA damage. Here we show that the TAp63α dimer is a kinetically trapped state. Activation follows a spring-loaded mechanism not requiring further translation of other cellular factors in oocytes and is associated with unfolding of the inhibitory structure that blocks the tetramerization interface. Using a combination of biophysical methods as well as cell and ovary culture experiments we explain how TAp63α is kept inactive in the absence of DNA damage but causes rapid oocyte elimination in response to a few DNA double strand breaks thereby acting as the key quality control factor in maternal reproduction.
Keywords: DNA damage; kinetically trapped state; p63; quality control; oocytes; spring-loaded activation